Implementation of Audio-Visual Based History Learning Media - Annisa Silviana Indriani; Muhammad Azmi (Yupa: Historical Studies Journal, 2025)
This study aims to determine the implementation of audio-visual-based History learning media in grades XI and XII of SMA Negeri 2 Loa Kulu, students' perceptions of its use, and the obstacles faced. This study uses a qualitative approach with a case study method, data collected through observation, structured interviews, and documentation. The results of this study indicate that audio-visual media such as History videos, PowerPoint, and digital content create interactive learning. Students' perceptions of audio-visual-based history learning media show good interest. The use of this media increases student involvement in the learning process and helps them understand history material in a concrete and interesting way. Students find it easier to understand the material and are more enthusiastic about participating in learning. However, in its implementation there are still obstacles, such as limited technological facilities, dependence on internet connections, and interference from classmates.